THE IMPLEMENTATION OF TEACHER BASED ASSESSMENT IN TEACHING SPEAKING SKILL - Linna Endah; Sholihin Hasan (Sekolah Tinggi Agama Islam Almuhammad Cepu, 2022)
ABSTRACTLecturer’s job is not only teaching but also assessing. The way a lecturer assesses the students’ achievement can be different one to others. In learning process, to know our students’ progress and improvement, we need “assessment”. Teacher-Based Assessment (TBA) is one of many kind of assessments in language teaching. TBA is an integral part of language instruction where the teachers, as “agents” (Rea-Dickins, 2004), are the ones responsible for facilitating student learning and obtaining information about their progress and achievement, hence, also earning the name “teacher assessment”. Unfortunately, there has not been a lot of studies on TBA implementation in Indonesia contexts. By conducting this study, the writers shared a new knowledge and experience in how TBA was conducted in teaching speaking for MPI’S students. The findings and discussion of this study showed that the MPI students could improve their speaking skill after the writer applied TBA (teacher-based assessment). The writer arranged her speaking class with some formation activities; for the examples; group discussion, presentation, and pair woks.Key words: teacher-based assessment, teaching, and speaking skill.